INOVASI KARTU SEGA SEBAGAI MEDIA PERMAINAN DALAM EDUKASI GIZI SEIMBANG DAN JAJANAN SEHAT ANAK SEKOLAH DI SDN 2 WATES TIMUR - Giziuap, Iissulastri (Poltekkes Kemenkes Riau, 2025)
Nutritional problems in school children are still quite complex, including overweight and obesity.The cause of nutritional problems in school-age children is unhealthy eating habits whichare also influenced by a lack of knowledge about nutrition. Community service activitiesare carried out to increase student knowledge and emphasize active student participationduring the implementation of activities. Community service was carried out at SDN 2 WatesTimur with a total of 28 fifth-grade students as respondents. The activities consisted of apreparation stage, namely screening and initial data collection, the implementation stageincluded a pre-test, delivery of materials and games using SEGA cards as media andevaluation, namely by giving a post-test. The results obtained showed that the respondentswere mostly female, aged 10-11 years and 11% of students were overweight and hadunhealthy snacking habits. Education was carried out using PowerPoint media followedby SEGA card games, which were obtained to attract active student participation and wereable to answer questions with the SEGA cards provided. Knowledge evaluation throughpre- and post-tests obtained an increase in knowledge of 31.7 points. The communityservice activities went well, were able to attract student activity and were able to increaseknowledge about balanced nutrition and healthy snacks.generations.